The role of ants in structuring insect communities on the canopies of senegalia drepanolobium near Laikipia, Kenya - Kuria, Simon Kamande (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2007)
In the black cotton ecosystem of Laikipia, Kenya, four symbiotic ants coexist at a fine spatial scale on canopies of Senegalia drepanolobium. They exhibit different aggressive behaviours and modify their tree canopies differently. These diverse behaviours were expected to affect the associated canopy arthropod communities. At the Kenya long-term exclosure experiment (KLEE) and its immediate environs at Mpala Research Centre, Laikipia, the insect communities coexisting with each of the four ant species were characterized, and their response to different vertebrate herbivory. Other ant species inhabiting the tree canopies or the ground were surveyed too. Pitfall trapping was used in sampling terrestrial ants, while beating and mist-blowing were used in collecting arboreal insects. Different sampling methods had varying efficacies, revealing the importance of using several methods. There are at least sixteen ant species in this ecosystem, all occurring on the ground, but only ten species on the trees. Terrestrial ant communities in this ecosystem cannot be used as indicators of grazing pressure for range management. A total of 10,145 individual insects were collected from the tree canopies, comprising of 117 species from seven orders and 25 families, forming a complex community of species interacting at different levels. Symbiotic ant species had a significant effect on insect community structure and composition. Crematogaster sjostedti was associated with a community that was significantly different from the other ant species. There was no significant effect of vertebrate feeding pressure on the canopy insect community, but there was an interaction effect between ant species and treatments. Significant differences between ant species mostly occurred on treatment plots where only cows were allowed to graze. One or more of the ant species may be a keystone species in this ecosystem even though experimental manipulations failed to confirm earlier findings. It was concluded that the one-year period during which experimental manipulations were carried out was not long enough to reflect takeover effects on the insect community. The four symbiotic ant species colonizing S. drepanolobium comprises of two guilds, the hemipteran-tending ants (C. sjostedti and Crematogaster mimosae) and non-tending ants (Crematogaster nigriceps and Tetraponera penzigi). Communities associated with these guilds were found to be significantly different in all four diversity indices. The black cotton ecosystem is species-poor compared to other ecosystem such as forests. The number of insect species that colonizes S. drepanolobium and coexists with acacia-ants forms a large proportion of the invertebrate community. Therefore, this ecosystem should be conserved to safeguard this invertebrate community. This will also give scientists a chance to establish how the various insect species coexist with symbiotic ants on tree canopies.
Keywords: Ants -- Kenya; Ants -- Behavior; Insect societies -- Kenya; Forest canopy ecology -- Kenya